Biochemical and physiological characteristics of pear fruit depending on position of fruit in tree - Stanivuković Sanda; Pašalić Boris; Đurić Gordana (Agroznanje, 2013)
Biochemical and physiological studies of pear fruit Packham's Triumph varieties at different positions (top, middle, base) and exposures (east, west) on the tree were made in pear orchards in Jurkovica - Gradiska municipality in the period 2010-2011. The trees of the studied cultivar were planted in a North - south direction, grown in the slender spindle training system on the wild pear seedlings. In the mentioned period they were in full fruiting period. The fruits were analized immediately after harvest and after a month of refrigerated storage with normal atmosphere. Analysis of variance showed that the flesh hardness and content of soluble solids in the fruit flesh is conditioned with fruit position in the tree, while exposition fruit didn't significantly affect the behavior of the fruit after harvest and after storage. The lowest hardness had the fruits from the peak zone while the highest value of the same parameter was observed in fruits from the base zone after harvest and after storage. The fruits from top zone had the highest content of soluble solids, but when it comes to the smallest content of the same there were some discrepancies by looking fruits after harvest and after storage. The fruits from middle zone had the lowest content of soluble solids after harvest. The same value was observed in fruits from the top zone after storage. Concerning the exposure aspect, the same behavior of fruits was observed. The results of the research are important for determination of fruits screening harvest and preserving the quality of stored fruits.